Comparison of Carbon Utilization Technologies for Decarbonization Strategy in the Ammonia Industry - Daril Ridho Zuchrillah; Rizal Arifin; Friska Dwi Pratiwi; Niken Rani Nastiti; Achmad Dwitama Karisma; Ardista Izdhihar Kaloka; Soeprijanto Soeprijanto (SINERGI, 2026)
Global climate change is caused by high greenhouse gas (GHG) emissions. The industrial sector is one of the most significant contributors of emissions, particulary from production activities and the use of fossil fuels. The ammonia (NH3) industry is an important chemical sub-sector that still relies on fossil fuels and contributes 1.6 tons of CO2 emissions per ton of ammonia production, accounting for nearly 2% of global carbon emissions. Therefore, Carbon Capture Utilization (CCU) technology is needed to support the decarbonization of the industry. This study uses Aspen Plus V14 software for process simulation. Three CO2 utilization pathways were simulated: methanol production (CH3OH), sodium bicarbonate production (NaHCO3), and methane production (CH4). The result show that converting CO2 into sodium bicarbonate (NaHCO3) yields the most favorable result with a profit of $65,277,360/year, a positive NPV of $840,647,028, an IRR exceeding the bank interest rate (10%) at 54%, and a POT in the fifth year. Additionally, sodium bicarbonate is environmentally sustainable, as evidenced by a CO2 emission reduction rate of 96%. The assessment was carried out under the assumptions of stable market conditions, sufficient availability of green hydrogen and ideal operating parameters, However, this study acknowledges inherent limitations, including catalyst performance, high energy requirements, and the challenge of integration with existing infrastructure, which may hinder large-scale implementation.